2017
DOI: 10.1016/j.cmi.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of respiratory syncytial virus infection among adults hospitalized with influenza-like illness in France

Abstract: RSV is an infrequent cause of ILI during periods of influenza virus circulation but can cause severe complications in hospitalized adults. Risk factors for RSV detection in adults hospitalized with ILI include cancer and immunosuppressive treatment. Specific immunization and antiviral therapy might benefit patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
74
6
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 23 publications
12
74
6
3
Order By: Relevance
“…This may suggest that influenza infection results in hospitalization for a relatively healthier group of adults 50-64 years old while RSV infection is more likely to result in hospitalization for those with multiple chronic conditions. A similarly designed study conducted in France over 3 seasons found that RSV cases were more likely to have cancer or be on immunosuppressive therapy than influenza cases [10]. Our findings provide evidence in support of focused development of RSV vaccines and therapies targeted toward an expanded age group of adults, particularly those 50-64 and those of any age with chronic comorbidities.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This may suggest that influenza infection results in hospitalization for a relatively healthier group of adults 50-64 years old while RSV infection is more likely to result in hospitalization for those with multiple chronic conditions. A similarly designed study conducted in France over 3 seasons found that RSV cases were more likely to have cancer or be on immunosuppressive therapy than influenza cases [10]. Our findings provide evidence in support of focused development of RSV vaccines and therapies targeted toward an expanded age group of adults, particularly those 50-64 and those of any age with chronic comorbidities.…”
Section: Discussionsupporting
confidence: 71%
“…However, unlike influenza, in which serious morbidity has been clearly recognized for years, the relative impact of RSV infection in adults has more recently gained widespread recognition [9,10]. While primary RSV infections in infancy can result in severe disease, subsequent infections are often comparatively mild.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality was equivalent between groups, with a similar percentage to that reported in previous studies. 7 The study has some limitations. It reflects only one winter season of analysis at a single healthcare center.…”
Section: Discussionmentioning
confidence: 98%
“…were hospitalized with a median length of stay of 5 days (IQR, [3][4][5][6][7][8][9][10][11][12]. The infection was healthcare related in 19% and nosocomial in 21% of cases.…”
Section: Characteristics Of Rsv-positive Patientsmentioning
confidence: 99%
See 1 more Smart Citation